Sinus augmentation with octacalcium phosphate–coated 100% cancellous bone mineral: Clinical case report - Lee, Myung Ho (Hasanuddin University, 2025)
Objective: This case report describes an attempt to improve regeneration outcomes for atrophied ridges using an octacalcium phosphate–coated deproteinized bovine bone mineral (DBBM) consisting of 100% cancellous bone, with the addition of adjuvant factors, including platelet concentrates (PC) and platelet-rich fibrin (PRF).Methods: A 53-year-old man presented with insufficient ridge height to support an implant following extraction of a fractured molar at FDI 16. Simultaneous implant placement and bone augmentation procedures were performed. An implant was placed in the remaining bone, and the defect was first filled with a coagulated mass comprising DBBM, PC, calcium, and thrombin and then covered with PRF.Results: No complications were recorded. A screw-retained temporary crown was placed after 4.5 months, and a final crown was replaced 3 months thereafter. Long-term stability was documented for over 11 years, based on radiographic images.Conclusion: This case study demonstrated the long-term safety and reliability of the xenograft to support bone regeneration and implant stability in a patient who was treated for alveolar bone loss.